Evaluation of a mobile NMR sensor for determining skin layers and locally estimating the T sub(2eff) relaxation time in the lower arm - Kornetka, Darius; Trammer, Martin; Zange, Jochen (Magma (New York, N.Y.), 2012)
Object: The nuclear magnetic resonance (NMR) mobile-universal-surface-explorer (MOUSE) was evaluated in a pilot study to determine its ability to detect physiological changes in human skin caused by physical or pharmacological interventions. Materials and methods: The left lower arm skin thicknesses of ten male subjects were measured five times using a Profile NMR-MOUSE super( registered ) ( super(1)H, 19 MHz) before and after a venous occlusion manoeuvre. In five of the subjects, the T sub(2eff) relaxation times were derived from a bi-exponential fitting and were determined in the dermis and subcutis before and after applying a salve containing capsaicin. Results: The dermis (including the epidermis) showed rather homogeneous signal amplitudes. The subcutis was characterised by higher and more variable amplitudes. The full-skin thickness values were affirmed by ultrasound imaging. The NMR profiles did not show significant skin swelling due to venous occlusion. In the dermis, capsaicin caused significant (p < 0.05) decreases in both components of T sub(2eff) (100 plus or minus 19 ms-19 plus or minus 10 ms; 9.5 plus or minus 0.5 ms-7.2 plus or minus 1.6 ms). In the subcutis, the T sub(2eff) was not affected. Conclusion: In principle, NMR-MOUSE profiles are capable of detecting skin structure. However, precise measurements are jeopardised by poor reproducibility, long acquisition times, and incompatibility between the geometries of the sensitive area of the instrument and the non-planar structure of the skin. In the dermis, T sub(2eff) contrast could be used to detect the changes in tissue composition caused by inflammatory reactions.